2007
DOI: 10.1021/nl0719832
|View full text |Cite
|
Sign up to set email alerts
|

Nonfunctionalized Nanocrystals Can Exploit a Cell's Active Transport Machinery Delivering Them to Specific Nuclear and Cytoplasmic Compartments

Abstract: We use high content cell analysis, live cell fluorescent imaging, and transmission electron microscopy approaches combined with inhibitors of cellular transport and nuclear import to conduct a systematic study of the mechanism of interaction of nonfunctionalized quantum dots (QDs) with live human blood monocyte-derived primary macrophages and cell lines of phagocytic, epithelial, and endothelial nature. Live human macrophages are shown to be able to rapidly uptake and accumulate QDs in distinct cellular compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
166
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(173 citation statements)
references
References 38 publications
7
166
0
Order By: Relevance
“…46 Our findings additionally confirm that the nuclear pore has a size-specific cutoff band of approximately 3.8 to 4.0 nm, even with paralyzed nuclear transport machinery. 30 We found that negatively charged SiO 2 -NPs did not infiltrate into the cytoplasm of both live cells (ie, untreated cells and those treated with Triton X) and fixed/permeabilized cells under static conditions. However, under the influence of SS, the SiO 2 -NPs were bound to the cell membrane in live cells and confined to the cytoplasm in fixed/permeabilized cells.…”
Section: Figurementioning
confidence: 75%
See 2 more Smart Citations
“…46 Our findings additionally confirm that the nuclear pore has a size-specific cutoff band of approximately 3.8 to 4.0 nm, even with paralyzed nuclear transport machinery. 30 We found that negatively charged SiO 2 -NPs did not infiltrate into the cytoplasm of both live cells (ie, untreated cells and those treated with Triton X) and fixed/permeabilized cells under static conditions. However, under the influence of SS, the SiO 2 -NPs were bound to the cell membrane in live cells and confined to the cytoplasm in fixed/permeabilized cells.…”
Section: Figurementioning
confidence: 75%
“…This is in agreement with the work of Nabiev and colleagues, who demonstrated that the surface protonation of CdTe-QDs in the endolysosomal compartment -followed by their reversible and pHdependent aggregation -was responsible for their escape into the cytoplasm. 30 This phenomenon could also be attributed to the possible interactions of CdTe-QDs with the cytoplasmic proteins, thereby forming a "protein corona" that gave them different biological properties and subsequently determined the fate of CdTe-QD localization.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Light microscopy and spectrometry (e.g. confocal microscopy and Raman spectroscopy) have proved indispensible for characterizing biological samples (Templeton et al, 2006;Nabiev et al, 2007;Jennifer et al, 2008). Light microscopy is compatible with in vivo characterization and provides three-dimensional (3D) information, although this technique is limited to a resolution of ∼100 nm (Guy & Colin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…5 Studies have shown that both negatively and positively charged QDs can be endocytosed, 6 and there is evidence that QDs exploit the cell's active-transport machineries for cytoplasmic and intranuclear delivery. 7 The major routes of human exposure to NP are transcutaneous, oral (enteric), or parenteral. Systemic delivery of NP-based therapeutic or diagnostic agents implies the interactions of NP with constituents of blood.…”
Section: Introductionmentioning
confidence: 99%